Proanthocyanidins (PC) - A novel approach - Jayamathi Govindaraj1 , Keerthidaa Govindaraj2 , S.Raghavendra Jayesh3 , Kesavaram Padmavathy4 , Mat (Indian Journal of Forensic Medicine & Toxicology, 2020)
An ever increasing number of pharmacological effects have become known through the discovery of newplant flavonoid with variations in chemical structure and related derivatives. A new group of phytochemicalsthat has been attracting much attention from both the general public and health professionals isa novel drugproanthocyanidins. This review emphasize various properties of proanthocyanidin, pertaining to variousdiseases of proanthocyanidins.